The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ijms18020457
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specificity of Mineralocorticoid Target Gene Expression during Renal Development, and Long-Term Consequences

Abstract: Sex differences have been identified in various biological processes, including hypertension. The mineralocorticoid signaling pathway is an important contributor to early arterial hypertension, however its sex-specific expression has been scarcely studied, particularly with respect to the kidney. Basal systolic blood pressure (SBP) and heart rate (HR) were measured in adult male and female mice. Renal gene expression studies of major players of mineralocorticoid signaling were performed at different developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…These contrasting findings could be due to different underlying mechanisms associated with chronic exposure to aldosterone versus acute blockade with a MR antagonist. Sex differences in memory functions related to MR function have been described in animal data (50) and sexually dimorphic regulation of the MR- and gender-specific effects of aldosterone are at least described for other tissues (51, 52).…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting findings could be due to different underlying mechanisms associated with chronic exposure to aldosterone versus acute blockade with a MR antagonist. Sex differences in memory functions related to MR function have been described in animal data (50) and sexually dimorphic regulation of the MR- and gender-specific effects of aldosterone are at least described for other tissues (51, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the regulatory mechanisms implicated in MR and GR expression, or their coregulators expression, could contribute to the emergence of a sexual dimorphism remain to be explored. Finally, to the best our knowledge, only one study has reported a sexual dimorphism for corticosteroid receptors expression in the kidney [ 77 ].…”
Section: Sexual Dimorphism Of Corticosteroid Signaling Aside From the Kidneymentioning
confidence: 99%
“…Sex steroids are known to influence the activity of the RAS in adults: testosterone promotes the action of Ang II via AT1R, whereas estrogen decreases the AT1R/AT2R ratio inducing a different receptivity to Ang II [ 103 ]. Our group observed a sex and organ-specific regulation of target genes of the corticosteroid signaling pathway in adult mice, along with a higher expression of renal 11βHSD2 in female mice, promoting the selectivity of aldosterone for its receptor [ 77 ]. This increased activation of the mineralocorticoid pathway in females does not increase blood pressure but could be aimed at a finer regulation of potassium excretion by distal tubules, which is an adaptive mechanism optimized for maternal–fetal homeostasis during pregnancy [ 106 ].…”
Section: Sexual Dimorphism In the Equilibrium Between Renal Mineralocorticoid And Glucocorticoid Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Systolic blood pressure (SBP) measurements were conducted in the animal facility of the FRIM (Fédération de Recherche en Imagerie Multi-Modalité, Paris-Diderot University, France) by tail-cuff plethysmography in trained and nonanesthetized animals as previously described 18 . Briefly, animals were acclimatized for at least 5 days before SBP measurements.…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%